Synthesis of shape memory alloy via annealing of electrodeposited layers of copper and tin on brass - Jagape, Jesse L. (2013)
A shape memory alloy (SMA) is a type of smart material that has the ability to recover its predetermined shape when exposed to an appropriate stimulus like temperature. A potentially inexpensive method of developing SMA is investigated in this study and this is through electrodeposition-and-annealing route. The study aims to synthesize a shape memory alloy from as-plated layers of tin and copper on brass strip. Initially, it was hypothesized that two possible SMAs can be produced from the heat-treatment of the mentioned system, and these are copper-tin (Cu-Sn) and copper-zinc-tin (Cu-Zn-Sn).The procedure for the development of SMA in the experiment involved four major steps: (1) substrate preparation; (2) electrodeposition of tin and copper on starting brass substrate; (3) furnace annealing, which involves pre-annealing, austenization, and quenching; and lastly, (4) flame testing for shape memory effect. The three parameters investigated in the current research were (1) tin content, (2) quenching medium, and (3) austenitizing temperature. The alloyed strips with significant shape recovery were subjected to thermal cycling, microstructural, elemental, phase, and thermal characterization for further analysis.Based on the results, the range of austenitizing temperature where significant shape recovery was observed was between 550C to 650C. In the tin content study, the results showed that increasing the tin concentration also increases the percent displacement of the bent alloyed strip during the flame test. However, varying the quenching medium and austenitizing temperature did not significantly affect the shape memory behavior. Furthermore, the synthesized strips exhibited no significant degradation in shape recovery after five thermal cycles. Meanwhile, the microstructure of the etched austenitized sample after cooling was viewed under the microscope, and it showed an intermetallic region with scalloped morphology. Using scanning electron microscope, the morphology revealed the presence of twinning, which is a distinct feature in the martensitic phase of SMA. The elemental analysis showed that some layers in the strip had compositions that corresponded with the -phase Cu-Zn-Sn. Conversly, the phase analysis of the alloyed strip further validated the presence of Cu-Zn-Snmartensite phase. Based on the thermal analysis, the transformation temperatures of the synthesized SMAs range from 224.9C to 226.6C for the austenite start temperature (AS), and between 221.5C and 223.1C for the martensite start temperature (MS).In summary, the analyses showed that the specific phase responsible for the shape recovery was a Cu-Zn-Sn SMA phase only. The failure to produce Cu-Sn SMA phase was attributed to the inappropriate composition of Cu0Sn alloy region and to the continuous interdiffusion of zinc towards the Cu-Sn layer.